Comportements comparés des marchés boursiers (1974-1979) - Bensoussan, Claude (L'Actualité économique)

(untitled) (HEC Montréal, 1981)
ABSTRACTThis article begins by pointing out, with regard to the study of stock market behaviour, the dangers of distortion inherent in factor analysis in principal components when applied as a method of grouping. As a follow-on to a preceeding contribution dealing with the period 1959-70 this article develops and clarifies the methodological aspects (dangers of factor analysis, utility of percolation method) within the context of the period 1974-79. The advantage of constituting groups from behaviourally homogenous markets, calculated according to the monthly variations in stock exchange rates of the 13 most important markets, is then analysed. The statistical analysis of links between national stock markets requires prudence as regards the use of notions in which the world stock markets are considered as being a whole, the concept of "economic blocks", indeed the same prudence must be exercised when considering the independence or interdependence of markets and the corresponding generalisations, although the long-term tendency would seem to have been modified since 1974 in a direction favourable to the empirical validation of the concept.